(untitled) (INNOVATIVE ECONOMY, 2024)
Yevchu S.A. INSTITUTIONAL ESSENCE OF THE SYSTEM OF AGRICULTURAL ADVISORY IN UKRAINE Purpose. The purpose of the article is the theoretical substantiation of the essence of modern agricultural advisory as a social and economic institution. Methodology of research. The theoretical and methodological basis of the research is an institutional approach using the methods of the theory of transaction costs and neo-institutional theory. The other methods were also used in the research process, in particular: statistical method – to assess the impact of informal institutions on the public perception of the agricultural advisory system; abstract and logical – for understanding the regularities of development of advisory; the method of institutional modelling – to determine the institutional components of the functioning of the agricultural advisory system. Findings. The theoretically grounded essence of modern agricultural advisory as a socio-economic institution, which provided an opportunity to determine its institutional structure, to deepen the types of functions performed by it, to expand the components that have an impact on the institutionalization of organizational formations of advisory. Originality. An institutional approach was used to substantiate the essence of modern agricultural advisory as a socio-economic institution, which creates the basis for a wider external perception of advisory. Practical value. The obtained research results are aimed at a wider external perception of the agricultural advisory system and create the basis for further in-depth improvement of scientific approaches and mechanisms in the development of concepts, rules, standards, functions, methods, management solutions for the implementation of professional agricultural advisory activities. Key words: institutional theory, institutionalism, institutions, environment, agricultural advisory system, advisory subjects, management system.